2017
DOI: 10.1123/ijsnem.2016-0259
|View full text |Cite
|
Sign up to set email alerts
|

Energy Intake and Expenditure of Professional Soccer Players of the English Premier League: Evidence of Carbohydrate Periodization

Abstract: In an attempt to better identify and inform the energy requirements of elite soccer players, we quantified the energy expenditure (EE) of players from the English Premier League (n = 6) via the doubly labeled water method (DLW) over a 7-day in-season period. Energy intake (EI) was also assessed using food diaries, supported by the remote food photographic method and 24 hr recalls. The 7-day period consisted of 5 training days (TD) and 2 match days (MD). Although mean daily EI (3186 ± 367 kcals) was not differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
152
7
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(176 citation statements)
references
References 35 publications
14
152
7
3
Order By: Relevance
“…When the two games per week schedule is taken into consideration, it is therefore unsurprising that the external training load (e.g. total distances of approximately 2 km) reported here is similar to those outfield players studied previously in the same micro-cycle 8 . In this regard, comparable markers of loading between positions are likely due to the fact that the outfield players have markedly reduced their training load when compared with the traditional one game per week schedule 5 .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…When the two games per week schedule is taken into consideration, it is therefore unsurprising that the external training load (e.g. total distances of approximately 2 km) reported here is similar to those outfield players studied previously in the same micro-cycle 8 . In this regard, comparable markers of loading between positions are likely due to the fact that the outfield players have markedly reduced their training load when compared with the traditional one game per week schedule 5 .…”
Section: Discussionsupporting
confidence: 74%
“…However, at the present time he was under no guidance from either the nutritionist or any of the teams support staff with regards to his nutritional nutritional intake. Interestingly, CHO intakes were increased from training (approximately 2.5 g.kg -1 body mass) to match days (3.5 g.kg -1 body mass), but not to as greater extent of the CHO periodisation strategies practiced by outfield players who increase their CHO intake on match days to > 6 g.kg -1 per day 8 . It is difficult to ascertain if the CHO strategy adopted by the GK studied here is conducive to optimal performance and hence further studies are required to examine the effects of specific dietary interventions on performance indices specific to elite GKs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This proportion was lower than that recommended for athletes under growing process and daily practice, to maximize muscular glycogen storage, carbohydrates should comprise 45% to 65% of total energy intake for 4-to 18-year-olds [27], in average of 6 to 10g/kg/day [28]. So, Anderson et al [29] suggested that although professional Soccer players readily achieve current guidelines for daily protein and fat intake, carbohydrates intake on the day before and in recovery from match play was not in accordance with guidelines to promote muscle glycogen storage.…”
Section: Discussionmentioning
confidence: 99%